Qualitative Data Collection, Analysis and Presentation: A Theoretical Overview - Uprety, Laya Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2010)
This paper explains the significance of the interpretive approach in the regime of qualitative research which underscores the search of the meanings in human cultures and subjectivities in the human behavior. Its overall emphasis has been on the processes, stages, and goals of conventional ethnographic research, qualitative data analysis and their presentation in the academic and professional reports. However, the theoretical analysis has been heavily influenced by "positivism" and hence, it has failed to address many of the issues emerged in the regime of contemporary qualitative research approach. Key Words: Qualitative; ethnographic; positivism; interpretive; subjectivity; analysis and presentation. DOI: 10.3126/dsaj.v3i0.2782 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 83-122